The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1002/ana.410440306
|View full text |Cite
|
Sign up to set email alerts
|

Time course of corticospinal excitability in reaction time and self‐paced movements

Abstract: We used transcranial magnetic stimulation (TMS) to study the time course of corticospinal excitability before and after brisk thumb abduction movements, either in a simple reaction time (RT) paradigm or self-paced. Premovement increase in corticospinal excitability began about 20 msec earlier for self-paced compared with simple RT movements. For both simple RT and self-paced movements after electromyographic (EMG) offset, there was a first period of increased excitability from 0 to 100 msec, followed by a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
255
2
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 365 publications
(301 citation statements)
references
References 44 publications
(16 reference statements)
40
255
2
4
Order By: Relevance
“…Levels of facilitation were rather feeble (110 % to 120 % of MEP amplitude at the onset of the IS) and not significantly different in both age groups. This result was in line with previous studies reporting increased CS excitability in the agonist muscle of the selected hand towards voluntary EMG onset in young adults (Chen et al 1998;Chen and Hallett 1999;Leocani et al 2000). In addition, no correlations were found between individual levels of facilitation at the 75 % PreMT and RTs (neither for older nor for young adults), indicating that higher facilitation of MEPs in the selected FDI did not necessarily predict faster RTs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Levels of facilitation were rather feeble (110 % to 120 % of MEP amplitude at the onset of the IS) and not significantly different in both age groups. This result was in line with previous studies reporting increased CS excitability in the agonist muscle of the selected hand towards voluntary EMG onset in young adults (Chen et al 1998;Chen and Hallett 1999;Leocani et al 2000). In addition, no correlations were found between individual levels of facilitation at the 75 % PreMT and RTs (neither for older nor for young adults), indicating that higher facilitation of MEPs in the selected FDI did not necessarily predict faster RTs.…”
Section: Discussionsupporting
confidence: 92%
“…It is assumed that suppression of CS excitability is necessary to prevent erroneous premature responding (Davranche et al 2007;Duque and Ivry 2009;Touge et al 1998). During response generation, however, it has been reported that CS excitability is increased in the agonist muscle of the selected hand towards voluntary electromyographical (EMG) signal onset (Chen et al 1998;Chen and Hallett 1999;Leocani et al 2000).…”
mentioning
confidence: 99%
“…A number of studies have previously demonstrated that stimulus intensities below resting motor threshold detected increases in CM excitability of an agonist during preparation for a motor action (Chen et al, 1998;MacKinnon and Rothwell, 2000;Pascual-Leone et al, 1992;Tomberg and Caramia, 1991). Indeed, in the present study, application of subthreshold TMS prior to intended muscle contractions in healthy subjects revealed that agonist BB CM excitability increased, because the stimulus intensities used were below rest threshold.…”
Section: Pre-contraction Modulation Of the Intact Antagonist Bbsupporting
confidence: 46%
“…Therefore, pre-contraction changes in CM excitability of the antagonist BB were assessed in the present study using stimulus intensities below resting threshold. Subthreshold TMS has been previously used to examine changes in CM excitability during preparation for a motor action in a number of studies (Chen et al, 1998;MacKinnon and Rothwell, 2000;Pascual-Leone et al, 1992;Tomberg and Caramia, 1991).…”
Section: Technical Considerationsmentioning
confidence: 99%
“…Motor cortex excitability is in¯uenced by multiple inputs that may vary depending on the task (Chen et al, 1998;Seyal et al, 1999), preparation for voluntary movement (Hoshiyama and Kakigi, 1999) and sensory input (Furubayashi et al, 2000;Tokimura et al, 2000). Electroencephalographic (Pfurtscheller et al, 1996;Leocani et al, 1997), magnetoencephalographic (Nagamine et al, 1994(Nagamine et al, , 1996 and event-related potentials (Shibasaki and Rothwell, 1999;Hoshiyama and Kakigi, 1999) evidence suggest premovement changes (bilateral in case of ERPs) hundreds of ms before and after a voluntary response.…”
Section: Introductionmentioning
confidence: 99%